6x+5-5x=12-27

Simple and best practice solution for 6x+5-5x=12-27 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6x+5-5x=12-27 equation:


Simplifying
6x + 5 + -5x = 12 + -27

Reorder the terms:
5 + 6x + -5x = 12 + -27

Combine like terms: 6x + -5x = 1x
5 + 1x = 12 + -27

Combine like terms: 12 + -27 = -15
5 + 1x = -15

Solving
5 + 1x = -15

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-5' to each side of the equation.
5 + -5 + 1x = -15 + -5

Combine like terms: 5 + -5 = 0
0 + 1x = -15 + -5
1x = -15 + -5

Combine like terms: -15 + -5 = -20
1x = -20

Divide each side by '1'.
x = -20

Simplifying
x = -20

See similar equations:

| 1.2x-7=0.04 | | Qr+rs=qs | | X+14=2x+11 | | 5x(15+5)=415 | | 16a^2-12a+3=0 | | 6(a-3)+4a=-68 | | x^2-9x=o | | 15-0.16n=0.16-1 | | 1.2x-3=0.04 | | -7(7x+9)+5= | | -14=-5+3b | | 7(m+2)+4(2m-3)=47 | | X+6+x=4x | | x(14+1)=3 | | 1.4x-7=0.06 | | AB+CB=DwhatsB | | x^3-2x^2-39x+72=0 | | 2x^3+15x^2+16x-12=0 | | 0.5(m-2)+0.6(m+3)=0.5(2m-4) | | (2x-6)(x+3)=2600 | | -3x+40=y | | 7=b+1 | | 12.890+0.12t=20 | | X+3x+2=q | | 33s+150=1000-150 | | 54677.23N=100000 | | 0.5(2x-3)-8=0.3(3x-4) | | abc=rfg | | 4x+2(x-6)=3x+5x+5 | | 14x+120-6x=200 | | 19x-8=9x-22 | | (10-3w)(w)=77 |

Equations solver categories